1997
DOI: 10.1074/jbc.272.7.4043
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Mast Cell Tryptase with Thrombin Receptors and PAR-2

Abstract: Tryptase is a serine protease secreted by mast cells that is able to activate other cells. In the present studies we have tested whether these responses could be mediated by thrombin receptors or PAR-2, two G-proteincoupled receptors that are activated by proteolysis. When added to a peptide corresponding to the N terminus of PAR-2, tryptase cleaved the peptide at the activating site, but at higher concentrations it also cleaved downstream, as did trypsin, a known activator of PAR-2. Thrombin, factor Xa, plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
418
1
5

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 556 publications
(439 citation statements)
references
References 41 publications
(51 reference statements)
15
418
1
5
Order By: Relevance
“…. ., were in accord with a previous study by Molino et al (1997). Our results indicated that tryptase was as e cient or more so than trypsin in hydrolyzing the P20 peptide to release SLIGRL, again in agreement with Molino et al (1997).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…. ., were in accord with a previous study by Molino et al (1997). Our results indicated that tryptase was as e cient or more so than trypsin in hydrolyzing the P20 peptide to release SLIGRL, again in agreement with Molino et al (1997).…”
Section: Discussionsupporting
confidence: 93%
“…However, some reports (Alm et al, 2000;Corvera et al, 1999;Molino et al, 1997;Schechter et al, 1998), but not others (Corvera et al, 1997;Steinho et al, 2000), have indicated that tryptase appears to behave as a partial agonist compared to trypsin for activating PAR 2 , implying that PAR 2 activation by tryptase may be in¯uenced by other factors. Interestingly, Huang et al (2001) demonstrated that recombinant bI-tryptase was unable to activate any of the PARs cloned to date, including PAR 2 expressed on HEK293 cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, increased expression of serine proteinases capable of activating PARs (Figure 1) has the potential to exacerbate inflammation. For example, PAR-2 can be activated by trypsin, mast cell tryptase (163), tissue factor-factor VIIa and factor Xa (15), some kallikreins (164), PR3 (165), and matriptase (166).…”
Section: Serine Proteinases and Cell Signalingmentioning
confidence: 99%